1998
DOI: 10.3109/10428199809058354
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of P-Glycoprotein and Leukocyte Differentiation Antigens in Chronic Myeloid Leukemia

Abstract: P-glycoprotein (Pgp) mediated multidrug resistance is often the cause of therapy failure in some tumors. Pgp expression was shown to have prognostic value in several hematological malignancies, especially in acute myeloblastic leukemia (AML) and acute lymphoblastic leukemia (ALL). In chronic myeloid leukemia (CML) Pgp is expressed by peripheral blood (PB) cells more often in the terminal disease stages (20-50% of patients have Pgp+ phenotype). Sequential studies show that Pgp+ cells often disappear from the PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…TMR and doxorubicin uptake into the cells was not modulated by inhibitors of either MDR1 or MRP1, thus indicating that, at least, ex‐vivo neither MDR1 nor MRP1 mediate the energy‐dependent exclusion of drugs from these cells. This confirms the report by Stavrovskaya et al (1998) on MDR1 functional activity in the peripheral blood of 12 patients in chronic phase and five patients in accelerated phase. None of these patients showed MDR1 activity, measured as rhodamine‐123 efflux sensitive to known MDR1 inhibitors (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…TMR and doxorubicin uptake into the cells was not modulated by inhibitors of either MDR1 or MRP1, thus indicating that, at least, ex‐vivo neither MDR1 nor MRP1 mediate the energy‐dependent exclusion of drugs from these cells. This confirms the report by Stavrovskaya et al (1998) on MDR1 functional activity in the peripheral blood of 12 patients in chronic phase and five patients in accelerated phase. None of these patients showed MDR1 activity, measured as rhodamine‐123 efflux sensitive to known MDR1 inhibitors (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…For example, it has been shown that ABCB1 expression can range from 0-100% in the chronic phase (CP) in CML patients [76,[162][163][164][165][166][167][168]. Several groups have reported that ABCB1 expression is higher in the blastic phase than the chronic phase [162,164,[167][168][169]. In contrast, other studies in CML patients have shown no significant difference of ABCB1 expression between the chronic and blastic phase [76,163,170].…”
Section: Abc Transporters In Hematological Malignanciesmentioning
confidence: 94%
“…8,9 These findings should stimulate further research to evaluate the addition of Pgp inhibitors to imatinib for the treatment of CML blastic crisis. …”
Section: Functional Consequence Of Mdr1 Expression On Imatinib Intracmentioning
confidence: 94%